Application programming interfaces speak louder than words: API Practices If You Hate Your Customers. - LIMONCELLI, THOMAS A. (Communications of the ACM, 2019)
A humorous article discusses various best practices for the use of application programming interfaces (API) by business enterprises and how they can negatively impact customer relations and public relations, particularly by not making APIs apparent on search engines.